Executive coaching for results : the definitive guide to developing organizational leaders - Underhill, Brian O., 1969-; McAnally, Kimcee, 1957-; Koriath, John J., 1953- (San Francisco : Berrett-Koehler Publishers : Ingram Publisher Services [distributor], 2007)
Includes bibliographical references (p. 157-158) and index